PENGARUH PENGGANTIAN SEBAGIAN RANSUM BASAL DENGAN TEPUNG DAUN PEPAYA (Carica papaya L) TERHADAP PERFORMANS AYAM PEDAGING - Tempomona, Sintia; Bagau, Betty; Wolayan, Fenny R.; Regar, Mursye N. (ZOOTEC, 2020)
EFFECT OF SUBTITUTION OF BASIC RATIONS WITH PAPAYA LEAF MEAL ON BROILER PERFORMANCE. Â This research aims to know the effect of substitution of basic rations with papaya leaf meal on broiler performance. Using 100 broiler chickens aged 2 weeks with an initial weight rate of 278.75 g. The design used was complete random design (CRD) consisting of 4 treatments and 5 replications. The arrangement of the treatment was as follows: R0 = 100% basal ration (RB) + 0% papaya leaf meal (PLM), R1 = 95% basal ration + 5% PLM, R2 = 90% basal ration + 10% PLM, R3 = 85% basal ration + 15% PLM. The results of the analysis of variance showed that the replacement of a portion of basal rations with papaya leaf meal had a significantly different (P < 0.05) on feed intake, daily weight gain and feed conversion. Based on the results of this study, It can be concluded that the using of papaya leaf meal can replace a portion of ration until 5% level.Keywords: Performance, papaya leaf meal, broiler chickens